SUSTAINABLE DEVELOPMENT OF TRADE: A THEORETICAL PERSPECTIVE - NIKOLAICHUK, Olha; LAVRONENKO , Hennadii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article highlights the theoretical aspect of sustainable trade development. It is found that trade development through more rational and efficient use of resources, production growth, increased income and investment leads to economic growth and employment. It is found that the sustainability of domestic trade is reflected primarily in its impact on human development. It is determined that the sustainable development of Ukraine's trade is laid down in the provisions of trade agreements between Ukraine and other countries and unions of countries. The author analyzes the features of the WTO agreement on sustainable trade development. The article analyzes the provisions of the EU-Ukraine Association Agreement in the area of trade policy development with regard to sustainable development. It is noted that trade is key to achieving the UN Sustainable Development Goals. It is found that the main direction of implementation of socio-economic management methods for sustainable trade development is performance management, which enhances the social orientation of management through the effect of activity and creates a system of motivation and incentives for labor. It has been found that trade is also important for social integration, which, along with the economy and the environment, is one of the three pillars of sustainable development. In Ukraine, environmental and sustainable development issues are poorly integrated into the process of formulating and implementing public policy, including trade policy. Therefore, environmental protection and sustainable development should be clearly enshrined in trade policy. The presence of environmental factors in a trade agreement cannot depend solely on the policies and approaches of the other party.
Keywords: trade; trade policy; sustainable development; governance; agreement